An Implication of Destination Attractiveness, Environmental Sensitivity, and Satisfaction with Interpretive Service on Place Attachment and Environmental Responsible Behavior - Fachri Eka Saputra; Wahyu Heryanto Putra (International Journal of Social Science and Business, 2020)
This study examines the effect of destination attractiveness, environmental sensitivity, and satisfaction with interpretive services on place attachment. This study also aims to identify the effect of place attachment on environmentally responsible behavior. This study was using a questionnaire as a data collection method. This study's total sample was 400 respondents. However, the number of questionnaires that can be processed as 398. The data were processed using PLS-SEM (Partial Least Square). The result was obtained in this study: destination attractiveness has a significant positive effect on place attachment;  environmental sensitivity has a significant positive effect on place attachment; satisfaction with interpretive services has a significant positive effect on place attachment; place attachment has a significant positive effect on environmentally responsible behavior; destination attractiveness has a significant positive effect on environmentally responsible behavior; environmental sensitivity has a significant positive effect on environmentally responsible behavior; satisfaction with interpretive services has a significant positive effect on environmentally responsible behavior. This research contributes to the literature on tourism marketing.